Pendampingan Teknis Pemeliharaan Struktur Instalasi Pengolahan Air Limbah (IPAL) Desa Leyangan Kabupaten Grobogan - Bagus Acung Billahi; Kukuh Wisnuaji Widiatmoko; Faizal Mahmud (Jurnal Pengabdian KOLABORATIF, 2025)
Leyangan Village is one of the villages in Central Java located in Penawangan District, Grobogan Regency, and Central Java Province. The location of the village is ±50.1 km from the Semarang University (USM) campus. Understanding and implementing SOPs for maintaining wastewater treatment plant structures is one of the problems Leyangan village residents face when they receive assistance in the form of domestic wastewater treatment installation facilities. This activity aims to increase the knowledge of the Leyangan village community regarding methods for maintaining wastewater treatment plant (IPAL) structures. It is necessary to provide explanations and assistance regarding the Leyangan Village wastewater treatment plant which can still function effectively and well and encourage the community to adopt clean and healthy living habits. Assistance is carried out by providing presentations, demonstrations, and direct practice regarding the maintenance of wastewater treatment plants. The result of the training activity is an increase in knowledge. Evaluation is carried out by looking at the results of the pre-test questionnaire and comparing it with the post-test questionnaire. At the beginning before training, the average level of knowledge of participants only reached 32%. However, after training and direct practice were carried out, the participants' knowledge increased to an average of 70%.